Hydrogen Sulfide Treatment Alleviates Chilling Injury in Cucumber Fruit by Regulating Antioxidant Capacity, Energy Metabolism and Proline Metabolism - Jingda Wang; Yaqin Zhao; Zhiqian Ma; Yonghua Zheng; Peng Jin (Foods, 2022)
Although low-temperature storage could maintain the quality of fruits and vegetables, it may also result in chilling injury (CI) in cold-sensitive produce, such as cucumbers. This can seriously affect their quality.” The antioxidant capacity, energy metabolism and proline metabolism of cucumbers treated with hydrogen sulfide (H2S) were studied in this assay. The outcomes displayed that H2S treatment effectively reduced CI and delayed the increase in electrolyte leakage (EL) and malondialdehyde (MDA) content. In addition, the H2S-treated cucumber fruit exhibited higher L* and hue angle values, as well as nutrients such as ascorbic acid (AsA). The H2S-treated fruit showed lower levels of reactive oxygen species (ROS) and higher antioxidant enzyme activities. Meanwhile, H2S treatment also increased the activities of the essential enzymes involved in energy metabolism, including cytochrome C oxidase (CCO), succinate dehydrogenase (SDH), H+-ATPase and Ca2+-ATPase, which improved the energy supply. H2S induced higher ornithine δ-aminotransferase (OAT) and Δ-1-pyrroline-5-carboxylate synthetase (P5CS) activities, and reduced proline dehydrogenase (PDH) activity, promoting the accumulation of proline. These results indicated that H2S could alleviate CI in the cucumber fruit by modulating antioxidant capacity, energy metabolism and proline metabolism, thereby extending the shelf life of postharvest cucumbers.